Mothering sweetness mixed with the bitterness of death: the lived mothering experience of near-miss mothers - Sedigheh Abdollahpour; Abbas Heydari; Hosein Ebrahimipour; Farhad Faridhoseini; Talat Khadivzadeh (Journal of Psychosomatic Obstetrics and Gynecology, 2022)
Purpose Maternal near miss (MNM) refers to women who survive death as a result of life-threatening obstetric complications or organ system dysfunction during pregnancy, childbirth or postpartum. The aim of the present study was to gain an understanding of mothering experiences in survivors ‘mothers due maternal near miss event. Materials and methods Heideggerian hermeneutic phenomenology guided this qualitative study. The study was conducted 1 June and 30 December 2019. The sampling was purposeful with maximum variation of 11 near miss mother that used unstructured face-to-face interview for data collection. Data analyzed using Diekelmann, Allen, and Tanner seven stage thematic analysis approach. Findings Emergent theme was “mothering sweetness mixed with the bitterness of death.” The two themes constituting the essence was: “An Angel with Broken Wings” and “Mothering in the Shadow of Death.” The subthemes comprised five sub-sub themes which emerged from over 850 meaning units. Data were analyzed using MAXQDA10 software. Conclusion Maternal health providers need to know that it is not enough only to focus on saving the mother’s physical life. While strengthening the role of mothering is essential element to support near-miss mothers who have experienced difficult physical and psychological conditions. The “beyond numbers” concept, implies that it is not enough only to focus on saving the mother’s physical life. Removing barriers in order to achieve to early mothering, can have a significant impact on reducing the psychological burden of MNM events.